IMPLEMENTATION OF HEALTH EDUCATION ON DIABETES FOOT EXERCISES USING BOOKLET MEDIA FOR A DIABETES MELLITUS SUFFERER IN KARANGTURI VILLAGE BANYUMAS REGENCY: CASE REPORT - Lusi Setiawati; Nuriya Nuriya; Ridlwan Kamaluddin; Agis Taufik (International Journal of Biomedical Nursing Review, 2025)
Introduction: Diabetes mellitus is also known as a "lifelong disease," but it can be managed. Indonesia ranks fifth in the world for the highest number of sufferers, with 19.5 million sufferers in 2021, and this number is predicted to increase by 2045. Management is needed to improve the quality of life and prevent complications in diabetes mellitus sufferers. Foot exercises are considered a simple treatment option, but many people are unfamiliar with it. Therefore, health education is needed using media that can increase knowledge, such as booklets. Objective: This study aims to determine the effect of implementing health education in the form of diabetic foot exercises using booklets as media on diabetes mellitus sufferers. Methods: This research method used a case report and the DKQ-24 (Diabetes Knowledge Questionnaire), a questionnaire assessing knowledge about diabetic foot exercises. Descriptive data analysis was then conducted by comparing pretest and posttest scores. Discussion: After health education using a booklet during one meeting and demonstration of diabetic foot exercises during three meetings, there was an increase in respondents' knowledge as evidenced by an increase in posttest results. Conclusion: Implementation of health education on diabetic foot exercises using booklets for Mrs. TM can increase the knowledge of diabetes mellitus sufferers.